An insight into track and field coaches` knowledge and use of sprinting drills to improve performance - Whelan, N.; Kenny, I. C.; Harrison, A. J. (International Journal of Sports Science & Coaching, 2016)
Coaches` knowledge of drills and their specificity to sprint movement patterns and muscle activations have become increasingly important. Drills are used to encourage the development of optimal movement and coordination. They are prescribed to help the athlete develop sprint technique, and it is generally assumed that the drills are the parts within a whole-part-whole learning strategy. Previous literature has suggested some drills may be questionable as they may not replicate the muscle activations or movement pattern of sprinting. A total of 209 coaches completed an online questionnaire, which examined coaches` choice of drills; reasons for using each drill and reasons for changing drills used. The results were analysed using qualitative and quantitative methods. Results showed that coaches believed that drills are a vital part of training to improve performance but that they should be specific to sprinting technique.